Long‐term response of temperate canopy trees to removal of browsing from an invasive arboreal herbivore in New Zealand. (18th July 2016) - Sweetapple, Peter J.; Nugent, Graham; Whitford, Jacqueline; Latham, M. Cecilia; Pekelharing, Kees
Abstract: Defoliation of forest tree canopies by herbivores and other agents, leading to tree mortality and reduced productivity, threatens the ecological stability of forests globally. This study shows that long‐term control of a mammalian arboreal folivore (brushtail possums; Trichosurus vulpecula Phalangeridae) reduces crown dieback and increases foliage cover in browsing‐damaged canopy trees. We monitored indices of possum density, possum browsing, tree foliage cover and crown dieback for 20 years following initiation of possum control in 1994 that repeatedly reduced possum densities to near zero every 5–6 years and kept the population below 35% of pre‐control levels over the entire period. Observable possum browsing was recorded on 20–49% of individuals of three palatable tree species at the time of first control. Those percentages fell to zero after control and never exceeded 2–10% for individual species over the next 19 years. We recorded significant increases in foliage cover attributable to recovery from defoliation by possums for all three species during the first 10 years. Large increases in foliage cover occurred on individuals that were heavily browsed in 1994 (mean increases: 36–89%), but mean population increases were modest (3–19%) because only 10–19% of trees were initially heavily browsed. Twenty‐year mortality rates were similar for plants with, or without, initial possum browsing, indicating no residual impact of pre‐control browsing on tree mortality. Times for full recovery of crown foliage cover varied from 10 years for the youngest trees and faster growing species to more than 20 years for mature individuals of the slowest growing species.